2019
DOI: 10.1038/s41467-019-10695-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of forward and backward locomotion through intersegmental feedback circuits in Drosophila larvae

Abstract: Animal locomotion requires spatiotemporally coordinated contraction of muscles throughout the body. Here, we investigate how contractions of antagonistic groups of muscles are intersegmentally coordinated during bidirectional crawling of Drosophila larvae. We identify two pairs of higher-order premotor excitatory interneurons present in each abdominal neuromere that intersegmentally provide feedback to the adjacent neuromere during motor propagation. The two feedback neuron pairs are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(104 citation statements)
references
References 58 publications
(77 reference statements)
0
93
0
Order By: Relevance
“…The connectome identifies inhibitory neurons making direct synaptic connections to motoneurons, including aCC (Clark et al, 2018, Kohsaka, 2019. We found that expression of NaChBac in all GABAergic neurons (Gad1-T2A-Gal4), as well as all cholinergic neurons (ChAT-BAC-Gal4), is lethal.…”
Section: Acc Receives Gabaergic Inputsmentioning
confidence: 89%
See 4 more Smart Citations
“…The connectome identifies inhibitory neurons making direct synaptic connections to motoneurons, including aCC (Clark et al, 2018, Kohsaka, 2019. We found that expression of NaChBac in all GABAergic neurons (Gad1-T2A-Gal4), as well as all cholinergic neurons (ChAT-BAC-Gal4), is lethal.…”
Section: Acc Receives Gabaergic Inputsmentioning
confidence: 89%
“…w -; +; Gad1-T2A-Gal4 / TM6b which expresses in all GABAergic neurons. Three different lines designed to target A23a: R78F07-Gal4 (Zarin et al 2019), R78F07-AD; R49C08-DBD split Gal4 and R41G07-AD; R78F07-DBD split Gal4 (also termed SS04495-Gal4) (Kohsaka et al, 2019). Three different lines designed to target A31k: R87H09-Gal4 (Zarin et al 2019), R20A03-AD; R87H09-DBD split Gal4 and R20A03-AD (Zarin, unpublished); R93B07-DBD split Gal4 (also termed SS04399-Gal4) (Kohsaka et al, 2019).…”
Section: Drosophila Rearing and Stocksmentioning
confidence: 99%
See 3 more Smart Citations